Lama Penggunaan Kontrasepsi Depo Medroksi Progesteron Asetat dengan Indeks Massa Tubuh dan Kadar Kolesterol Total - Suratiah Suratiah; Nengah Runiari; Dewa Ayu Ketut Surinati; Ni Nyoman Hartati; Dewa Made Ruspawan (Jurnal Gema Keperawatan, 2021)
BMI and total blood cholesterol levels in Depo Medroxy Progesteron Asetate family planning users in the work area of Puskesmas IV Denpasar Selatan in 2021. This study used a non-probability sampling technique with purposive sampling as many as 32 respondents. Collecting instruments through interviews and measuring Basal Metabolisme Indekx by measuring height and weight and measuring cholesterol levels using the EasyTouch GCU Kit. The results showed that most of the users of injection contraceptive Depo Medroxy Progesteron Asetate were 22 people 68.8% ≥24 months, most of the users of Depo Medroxy Progesteron Asetate injection contraception had a heavy Basal Metabolisme Indekx 40.6%  and cholesterol normal levels 68.8%, rather high cholesterol 25.0% and high cholesterol 6.3%. Hypothesis testing used is the contingency coefficient with a Basal Metabolisme Indekx value of p = 0.001 (p0.05) and a cholesterol value of p = 0.037 (p0.05), so there is a relationship between the length of time using Depo Medroxy Progesteron Asetate injection contraceptives and Basal Metabolisme Indekx. and total cholesterol levels in the blood in Depo Medroxy Progesteron Asetate family planning acceptors users in the work area of Puskesmas IV South Denpasar in 2021. Based on the results of the study, it is hoped that this can be taken into consideration in providing education and counseling on how to overcome the side effects that occur, so that family planning acceptors Depo Medroxy Progesteron Asetate contraceptives are the only hormonal contraceptives that consistently have an effect on weight gain which results in changes in BMI and affects the lipid profile resulting in increased cholesterol levels. The purpose of this study was to determine the relationship between the duration of use of DMPA injection contraceptives with can overcome the problem of increasing. weight arising from the use of Depo Medroxy Progesteron Asetate family planning and the importance of measuring cholesterol levels regularly in Depo Medroxy Progesteron Asetate family planning acceptors.